Peroxisome Proliferator-Activated Receptor-γ Modulates the Response of Macrophages to Lipopolysaccharide and Glucocorticoids - Heming, Michael; Gran, Sandra; Jauch, Saskia-L.; Fischer-Riepe, Lena; Russo, Antonella; Klotz, Luisa; Hermann, Sven; Schäfers, Michael; Roth, Johannes; Barczyk-Kahlert, Katarzyna (Frontiers in Immunology, 2018)
Although glucocorticoids (GC) represent the most frequently used immunosuppressive drugs, their effects are still not well understood. In our previous studies, we have shown that treatment of monocytes with GC does not cause a global suppression of monocytic effector functions, but rather induces differentiation of a specific anti-inflammatory phenotype. The anti-inflammatory role of PPAR-γ has been extensively studied during recent years. However, a relationship between GC treatment and PPAR-γ expression in macrophages has not been investigated so far. Studies using PPAR-γ-deficient mice have frequently provided controversial results. A potential reason is the use of primary cells, which commonly represent inhomogeneous populations burdened with side effects and influenced by bystander cells. To overcome this constraint, we established ER-Hoxb8-immortalized bone marrow-derived macrophages from Ppargfl/fl and LysM-Cre Ppargfl/fl mice in this study. In contrast to primary macrophages, the ER-Hoxb8 system allows the generation of a homogeneous and well-defined population of resting macrophages. We could show that the loss of PPAR-γ resulted in delayed kinetic of differentiation of monocytes into macrophages as assessed by reduced F4/80, but increased Ly6C expression in early phases of differentiation. As expected, PPAR-γ-deficient macrophages displayed an increased pro-inflammatory phenotype upon long-term LPS stimulation characterized by an elevated production of pro-inflammatory cytokines TNF-α, IL1-β, IL-6, IL-12 and a reduced production of anti-inflammatory cytokine IL-10 compared to PPAR-γ WT cells. Moreover, PPAR-γ-deficient macrophages showed impaired phagocytosis. GC treatment of macrophages led to the upregulation of PPAR-γ expression. However, there were no differences in GC-induced suppression of cytokines between both cell types, implicating a PPAR-γ-independent mechanism. Intriguingly, GC treatment resulted in an increased in vitro migration only in PPAR-γ-deficient macrophages. Performing a newly developed in vivo cell tracking experiment, we could confirm that GC induces an increased recruitment of PPAR-γ KO, but not PPAR-γ WT macrophages to the site of inflammation. Our findings suggest a specific effect of PPAR-γ on GC-induced migration in macrophages. In conclusion, we could demonstrate that PPAR-γ exerts anti-inflammatory activities and shapes macrophage functions. Moreover, we identified a molecular link between GC and PPAR-γ and could show for the first time that PPAR-γ modulates GC-induced migration in macrophages.